Solution-processed perovskite light emitting diodes with efficiency exceeding 15% through additive-controlled nanostructure tailoring - Muyang Ban (Nature Portfolio, 2018)
Crystal sizes play a vital role in pushing up the efficiency of organometal halide perovskites based LEDs. Here Ban et al. incorporate a molecular additive to control the crystallite distribution and phase separation in the perovskite devices, resulting in high external quantum efficiency of 15.5%.